(untitled) - Applegate, Lynda M.; Lynda M. Applegate; Robert D. Austin; F. Warren McFarlan (Boston)
Harvard Business School Cases are world renowned for their extensive and thorough exploration of strategic issues. We are offering a selection of recent HBS cases with four module introductions as a stand-alone product for the first time to offer greater flexibility for packaging with other MH/Irwin products. This book is written for students and managers who desire an overview of e-business and contemporary information systems technology (IT) management
Includes bibliographical references and index
Keywords: Electronic commerce; Business; Internet